Situation Report: Bulgaria, 26 June 1975 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Efforts to Counter the "Gray Stream" Lyudmila Zhivkova Appointed to Top Cultural Post The 1975 Tourist Season Opens Bulgaria Reportedly Asks Bonn for Large Credit Bulgarian-Greek Relations on the Eve of Karamanlis Visit